Perioperative Management for Microsurgical Free Tissue Transfer: Survey of Current Practices with a Comparison to the Literature - Motakef, Saba; Mountziaris, Paschalia M.; Ismail, Inzhili K.; Agag, Richard L.; Patel, Ashit (Journal of Reconstructive Microsurgery, 2015)
Background Free tissue transfer is an important technique in reconstructive surgery. Due to a lack of evidence-based guidelines, a variety of practices are currently implemented by microsurgeons. This motivated the authors to define current practices and identify key areas where these practices can be optimized.Methods An anonymous online survey consisting of 40 questions regarding perioperative management for free tissue transfer was generated via an online survey platform. Questions covered topics including patient selection, anesthesia, patient temperature, fluid management, vasoactive agents, and analgesia. Approval was received from the American Society for Reconstructive Microsurgery and the survey was distributed to its members via two emails, in May and June 2013.Results Survey responses were received from 82/706 microsurgeons (12% response rate): 36% of respondents believed that complications of these cases are “sometimes” or “often” related to anesthesia; 55% of respondents stated they do not use specific goals and protocols to guide fluid management for these cases; 38% of respondents stated that they have no target range for hemoglobin and hematocrit for these procedures; and 70% of respondents stated that they do not permit the use of a vasopressor in nonemergent situations.Conclusion Current practices remain exceedingly diverse and at times differ from best practices, which may be identified from the available literature. Key areas where patient care can be standardized and optimized include anesthesia, patient temperature, fluid management, the use of vasoactive agents, and analgesic medications. Standardized, evidence-based guidelines have the potential to further improve patient care and free flap outcomes.
Keywords: free flap; free tissue transfer; vasopressors; microsurgery; perioperative management; anesthesia; temperature; fluid management